FabH Mutations Confer Resistance to FabF-Directed Antibiotics in Staphylococcus aureus - Parsons, Joshua B. (Antimicrob Agents Chemother, 2015)
Delineating the mechanisms for genetically acquired antibiotic resistance is a robust approach to target validation and anticipates the evolution of clinical drug resistance. This study defines a spectrum of mutations in fabH that render Staphylococcus aureus resistant to multiple natural products known to inhibit the elongation condensing enzyme (FabF) of bacterial type II fatty acid synthesis. Twenty independently isolated clones resistant to platensimycin, platencin, or thiolactomycin were isolated. All mutants selected against one antibiotic were cross-resistant to the other two antibiotics. Mutations were not detected in fabF, but the resistant strains harbored missense mutations in fabH. The altered amino acids clustered in and around the FabH active-site tunnel. The mutant FabH proteins were catalytically compromised based on the low activities of the purified enzymes, a fatty acid-dependent growth phenotype, and elevated expression of the fabHF operon in the mutant strains. Independent manipulation of fabF and fabH expression levels showed that the FabH/FabF activity ratio was a major determinant of antibiotic sensitivity. Missense mutations that reduce FabH activity are sufficient to confer resistance to multiple antibiotics that bind to the FabF acyl-enzyme intermediate in S. aureus.